Seed Germination and Response of Stem-cuttings to Hormonal Treatment in Six Priority Wild Edible Fruit Species of Sikkim Himalaya - Sundriyal, Manju; Sundriyal, R. C. (Indian Forester, 2001)
The present study was undedaken with the objectives to study germination and vegetative propagation of six most preferred wild edible fruit species, which bear maximum biotic pressure in natural habitats in the Sikkim Himalaya. All the species had fairly good seed germination (70-100%} except for Baccaurea sapida (34-50%). Seeds of Spondias axillaris showed viability up to 390 days, Machilus edulis 250 days, B. sapida 150-180 days, Eleagnus latirolia 70 days and Diploknema butyracea 50 days. Observations on stem sprouting and rooting were made in different seasons after treating stem cuttings with growth hormones, and it varied significantly among species. For Diploknema butyracea, 75% stem cuttings recorded sprouted while for Eriolobus indica and Eleagnus latifolia only <40% stem cuttings sprouted. Increased concentration ofIAA, IRA and NAA adversely affected sprouting of all the species. No sprouting was recorded for Machilus edulis and Baccaurea sapida in any treatment as well as in control set. It was recorded that though the species have good germination at nursery condition, the plant dwellers collect maximum fruits from all accessible locations from wild forest stands. To conserve species from over-exploitation, these species need to be included in afforestation programmes and in agroforestry systems so that farmers may get better economic returns from them, at the same time species may be protected in natural habitats.